(untitled) (Research, Society and Development, 2020)
The objective of this study was to identify the repercussions of good neonatal practices from the birth care profile. A quantitative, descriptive, documentary and retrospective study conducted with the verification of 1062 electronic medical records of pregnant women who were attended at the time in delivery in a low risk maternity, from June 2018 to May 2019. For the analysis were performed relative frequencies and absolute values also a Chi-square test was applied. Significant differences were considered, with results of p <0.05. Most newborns had good vitality at birth, timing of umbilical cord clamping and breastfeeding in the first hour of life were practices associated to the professional nurse and there was an association between newborns who suckled in the first hour of life and maintained exclusive breastfeeding throughout the lenght stay.